Stability Analysis of VSC back-to-back link taking into consideration adjacent AC systems of arbitrary configuration; Innovative Smart Grid Technologies Conference Europe (ISGT Europe), IEEE PES - Berkh I. V. Igor Vladimirovich; Lozinova N. Natalya; Ufa R. A. Ruslan Alexandrovich; Suslova O. V. Olga Vladimirovna; Andreev M. V. Mikhail Vladimirovich; Suvorov A. A. Aleksey Aleksandrovich; Ruban N. Yu. Nikolay Yurievich (2019, 2019)
Title screen